Kinetic modeling of H-mode pedestal with effects from anomalous transport and MHD stability - Pan’kin, A.Y.; Park, G.Y.; Cummings, J.; Chang, C.S.; Bateman, G.; Bunner, D.; Groebner, R.J.; Hughes, J.W.; LaBombard, B.; Terry, J.L.; Kritz, A.H.; Ku, S.; et al. (Вопросы атомной науки и техники, 2011)
Scaling of the H-mode pedestal in tokamak plasmas with type I ELMs and dependence of the pedestal properties and the resulting divertor head load width with the plasma elongation and plasma current are investigated using the kinetic neoclassical XGC0 code for DIII-D and Alcator C-Mod tokamaks. The simulations in this study use realistic diverted geometry and are self-consistent with the inclusion of kinetic neoclassical physics, theory-based anomalous transport models with the E×B flow shearing effects, as well as an MHD ELM triggering criterion. Scalings for the pedestal width and height are developed as a function of the scanned plasma parameters. The nonlinear interplay between anomalous and neoclassical effects motivates the development of a self-consistent simulation model that includes neoclassical and anomalous effects simultaneously. It is demonstrated that the divertor heat load width depend on the plasma currents. In the development of this dependence, effects of neutral collisions and anomalous transport are taken into account. Changes in the neoclassical divertor heat load fluxes associated with the introduction of the neutral collision and anomalous transport effects are described. За допомогою кінетичного неокласичного коду XGC0 для розрядів в токамаках DIII-D і Alcator C-Mod досліджено скейлінг п’єдесталу в плазмі, що перебуває в режимі поліпшеного утримання, з прикордонними локалізованими модами (ПЛМ) першого типу, властивості п’єдесталу і потоку тепла на дивертор в залежності від витягнутості плазми та струму плазми. У розрахунках використовуються: реалістична геометрія дивертора, кінетична модель для неокласичних ефектів, модель аномального транспорту, яка враховує ефекти шира (ExB)-потоків, і умови збудження ПЛМ-нестійкостей. У результаті розрахунків отримані скейлінгі для ширини і висоти п’єдесталу як функції параметрів плазми. Нелінійна взаємодія неокласичних ефектів і ефектів, пов'язаних з аномальним транспортом, є мотивацією для розробки самоузгодженої чисельної моделі, яка одночасно включає ефекти аномального і неокласичного транспорту. Показано, що потоки тепла на дивертор залежать від плазмових струмів. Також представлено результати дослідження залежності напівширини профілів тепла на дивертор від ефектів, пов'язаних з аномальним транспортом і зіткненнями з нейтральними частинками. С помощью кинетического неоклассического кода XGC0 для разрядов в токамаках DIII-D и Alcator C-Mod исследованы скэйлинг пьедестала в плазме, находящейся в режиме улучшенного удержания, с приграничными локализованными модами (ПЛМ) первого типа, и зависимость свойств пьедестала и потока тепла на дивертор от вытянутости плазмы и тока плазмы. В расчетах используются: реалистичная геометрия дивертора, кинетическая модель для неоклассических эффектов, модель аномального транспорта, которая учитывает эффекты шира (ExB)-потоков, и условия возбуждения ПЛМ-неустойчивостей. В результате расчетов получены скэйлинги для ширины и высоты пьедестала как функции параметров плазмы. Нелинейное взаимодействие неоклассических эффектов и эффектов, связанных с аномальным транспортом, является мотивацией разработки самосогласованной численной модели, которая одновременно включает эффекты аномального и неоклассического транспорта. Показано, что потоки тепла на дивертор зависят от плазменных токов. Также представлены результаты исследования зависимости полуширины профилей тепла на дивертор от эффектов, связанных с аномальным транспортом и столкновениями с нейтральными частицами.